PROBABILITAS PULIH PADA BALITA KURUS DAN KURUS SEKALI MENURUT KEPATUHAN MENGIKUTI PEMULIHAN SECARA RAWAT JALAN DI KLINIK GIZI BOGOR - Sri Muljati; Heryudarini Heryudarini; Reviana Reviana; Effendi Rustam (Persagi, 2007)
THE PROBABILITY OF NUTRITIONAL STATUS IMPROVEMENT AMONG WASTING CHILDREN ACCORDING TO ROUTINE VISITS TO KLINIK GIZI BOGOR.Background: Prevalence of malnutrition on todler in Indonesia still high. It's an indication that nutrition prevention is not yet safisfiying. SKRT 2004 data shows that 9.3% todler in the cities and 11.1% In the village include in category at thin and very thin. Data from departement of health of RI 2005, Prevalence of malnutrition on todler is still on 19.2% and severe malnutrition is 8.8%. Bogor nutritional clinic is already develop severe malnutrition treament by out patient.Aims: To analize data of nutritional clinic visitors on 2001-2005. To now the probability of cured until Z_skore ≥ -2.5 SD dan Z_skore ≥ -2.0 SD, by using weight for height index on thin todlers and very thin todlers after six months of treatment. Methods: 294 todlers are devided in to two categories, which are 192 thin subject (≥-3SD s/d <-2 SD) and 102 very thin (<-3 SD) or thin with clinical indication. Inclution criteria in this anallsis, that the subject doesn't have such as down syndrome, heart disorder, thalasemia, hydrocephalus and microcephalus. Results: The study revealed that father education, mother age, todler age and compliance of treatment were correlated with probability of cured until Z_skore ≥ -2.5 SD dan Z_skore ≥ -2.0 SD, on thin todlers and very thin todlers after six months of treatment.Keywords: severe wasting, under five years, compliance